Application of WERA Radar to the Study of Current Monitoring in Taiwan - Yung fang, Chiu; Ching ho, Su; Yang Yih, Chen; Chen Ta, Li; chia ying, Chang (International Journal of Engineering and Technology, 2018)
The Wave Radar(WERA) system is a shore-based distant sensing system used to overswee ocean surface currents, waves, and wind courses taken by moving objects. The analyzed data span the year 2015. The residual state of circulation is characterized by two different zones separated by approximately 100 m isobaths. In the offshore region the residual currents have a significant dedication to the wind-driven part, while the nearshore region is characterized by a very strong time-independent residual state circulation, featuring one measured anticyclonic eddy north of Taiwan. The acquisition data and demonstrated achievements might be useful for a copy-proof area-defined boundary design and studies of the tidal fronts, local eddy dynamics , and passive tracer carried from one place to another within the area.The measuring effects are shown in the form of a dimensional map of the current velocity vectors in the examination area (with size of 10 Ã— 10 km2). Some characteristics of the current dimensional and temporal qualities in coastal waters are shown. In particular, the eddy-like constitutions (a few kilometers in diameter) rapidly rise and fall. Because similar eddies are discovered using contact measurement methods, the intricate and variable construction of the surface currents shown through the measurement radar does not appear to be an artefact.Â Â